THE ROLE OF ENGLISH COMMUNICATION IN TRAVEL INDUSTRY PROFESSIONAL INTERNSHIP EXPERIENCE - Andriani, Noni; Fidyaloka, Fitri Farhani; Siloto, Alisia Hamidah; Kristiana, Vera (Fakultas Sastra UMN AL Washliyah, 2025)
This research explores the central role of communication English in the internship experience of English Literature students in the tourism sector. Using a qualitative approach, this study aims to understand how students apply their English language skills in a real work context, and how those skills contribute to their success in internships. Through a case study, this research analyzes the internship experience of a student at an international travel company. Research results show that English language skills are not only important to communicate effectively, but also to build a positive image of the company and strengthen professional networks. This research highlights The importance of preparing students with comprehensive communication skills, including the ability to adapt to various communication contexts and understand different cultural nuances.